ANTICONVULSANT ACTIVITY OF ETHANOL LEAF EXTRACT OF Clerodendrum capitatum (VERBENACEAE) IN MICE AND CHICKS - OLORUKOOBA, A. B.; KOGUNA, M. A; ADAMU, A (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2020)
Clerodendrum capitatum is used in traditional folk medicine to manage a plethora of diseases including tuberculosis, epilepsy, fever, obesity, diabetes mellitus, diarrhea, asthma, hypertension, and erectile dysfunction. The main objective of this study was to evaluate the anticonvulsant activity of the ethanol leaf extract of Clerodendrum capitatum. Preliminary phytochemical screening and acute toxicity studies were conducted. Anticonvulsant activity was evaluated in mice and chicks using pentylenetetrazole, strychnine and maximal electroshock-induced convulsion models at doses of 100, 200 and 400 mg/kg. The oral median lethal dose of the plant was estimated to be greater than 5,000 mg/kg. The ethanol leaf extract of Clerodendrum capitatum at all tested doses significantly (p<0.05) delayed the onset of pentylenetetrazole-induced seizures in mice providing percentage protection of 33.33% at the 100 and 200 mg/kg doses respectively. In the strychnine-induced seizure model, the extract significantly (p<0.05) increased the mean onset of seizures at 200 and 400 mg/kg doses, however only the 400 mg/kg dose produced 16.67% protection against seizures. The extract at all doses did not protect the chicks from maximal electroshock-induced convulsions. Phytochemical screening of the ethanol leaf extract of Clerodendrum capitatum revealed the presence of phytochemical constituents including alkaloids, flavonoids, tannins, carbohydrates, cardiac glycosides, anthraquinones and steroids. The results obtained from this study suggests that the plant possesses anticonvulsant activity validating its traditional use in the management of epilepsy.